2018
DOI: 10.1155/2018/3948245
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Adequate Digoxin Dosage: An Application of Machine Learning Approach

Abstract: Digoxin is a high-alert medication because of its narrow therapeutic range and high drug-to-drug interactions (DDIs). Approximately 50% of digoxin toxicity cases are preventable, which motivated us to improve the treatment outcomes of digoxin. The objective of this study is to apply machine learning techniques to predict the appropriateness of initial digoxin dosage. A total of 307 inpatients who had their conditions treated with digoxin between 2004 and 2013 at a medical center in Taiwan were collected in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…Some studies used AI to predict the dosage of medicines such as insulin, digoxin, and warfarin [ 85 , 89 , 91 , 95 ]. AI in drug safety was also used to scan through the hospital’s EHR data and identify medication errors (ie, wrong medication prescriptions) [ 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies used AI to predict the dosage of medicines such as insulin, digoxin, and warfarin [ 85 , 89 , 91 , 95 ]. AI in drug safety was also used to scan through the hospital’s EHR data and identify medication errors (ie, wrong medication prescriptions) [ 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…12 Hu et al, in a study on prediction of digoxin dosage found that machine learning models can accurately predict initial digoxin dose and help clinicians in safe use of digoxin. 14 Yao et al, found that machine learning algorithms are the best alternatives to predict serum digoxin concentrations whenever blood samples from newborn infants for therapeutic drug monitoring are not available. 15 Goicoechea et al, has found that machine learning models can be helpful in interpretation of plasma concentrations of antiretrovirals in therapeutic drug monitoring.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a dose of digoxin that is too high for a patient can cause severe toxicity and even death. Only two and a half times a normal dosage of digoxin can be fatal in 50% of patients (Burns, 1999;Hu et al, 2018). NTI drugs are especially dangerous in patients that are elderly, have multiple illnesses, or are receiving multiple drugs (Burns, 1999).…”
Section: Therapeutic Indexmentioning
confidence: 99%